(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article examines the strategy for improving the efficiency of pilgrimage tourism based on marketing research, which examines the need for a radical improvement in the system of providing tourism services to increase the potential of tourism, further measures to increase the potential of domestic tourism. and foreign tourism, and also indicates comprehensive measures to solve the main problems in the field of tourism, the need to develop an action plan and other issues.